A fauna de Doryctinae (Hymenoptera: Braconidae) em remanescentes de Mata Atlântica Ombrófila Densa - Nunes, Juliano Fiorelini (2007)
Keystone species include parasitic wasps, which are natural enemies of phytophagous insects. The Atlantic Rain Forest holds an astonishing abundance of Doryctinae subfamily (Hymenoptera: Braconidae), and this study focused on this group due to its potential indicating environmental changes and its understudied diversity. The sampling sites were designed by the project: Richness and Diversity of Hymenoptera and Isoptera along a latitudinal gradient in Atlantic Rain Forest the pluvial eastern forest from Brazil (BIOTA/FAPESP-Process nº. 1998/05083-0). It was employed three sampling techniques: Malaise traps (passive sample method), Moericke traps (attractive one) and sweeping of vegetation (active one). A single sampling pattern was established to allow the comparison among methods. Doryctinae was identified in the generic level; the occurrence frequency and Diversity and Evenness Indexes were calculated to verify the distribution of Doryctinae in Atlantic Rain Forest. Linear and polynomial regressions were applied to the dispersion curves to verify correlations among data and latitudinal gradient in the Atlantic Rain Forest. The total specimens captured were 12,249, identified in 41 genera, six recorded as new. Santa Lúcia Biological Station, at Santa Teresa district (ES) showed the highest occurrence frequency of Doryctinae specimens, 13.5% (1.651) and genera richness (23). The highest values of Diversity Index were found at Santa Luzia do Itanhy (SE) and Santa Maria Madalena (RJ) (1.02 nats). São Bento do Sul (SC) was the more homogeneous site (52.15% of Evenness). Heterospilus Haliday was the more abundant genus, with more than 80% of the total specimens captured (10.154). Santa Teresa (ES) was the site with more exclusive genera, six. Two new exclusive genera was identified at Santa Maria Madalena (RJ) (Gênero Novo 2 e Gênero Novo 4), as well as at Santa Luzia do Itanhy (SE) (Gênero Novo 5 e Gênero Novo 6) and at Mata de São João (BA) (Gênero Novo 3). Sweeping of vegetation was the technique with more specimens captured (8,566) and more different genera identified (37). Trends lines obtained by simple linear regressions indicated no association among latitude and analyzed variables. In applied polynomial trend lines, suggested a latitudinal pattern for the Doryctinae, which showed high values of abundance, richness and diversity at median latitudes, between 15ºS and 20ºS. The total number of the Doryctinae valid genera until now is 179; from those, 97 occur in Neotropical region and 80 in Brazil, where the greatest number of genera records is found. 29 new genera from Brazil were confirmed, however not published yet. Diagnose of six new genera from the Atlantic Rain Forest is presented as well as their position on the identification guide of Doryctinae genera from the New World (MARSH, 1997). Although only 7% of its original vegetal cover is left, we verify an abundant and genera-rich Doryctinae community in Atlantic Rain Forest.